An analysis of sections 11D(1)(A) and 11D(5)(B) of the income tax Act No. 58 of 1962 as amended - Strauss, Carien (Stellenbosch : Stellenbosch University, 2011)
Thesis (MAcc)--Stellenbosch University, 2011.